The Position of Local Religions in Interfaith Relations as a Form of Religious Moderation in Indonesia - Daffa, Muhammad; Anggara, Indra (Indonesian Journal of Religion and Society, 2023)
The Constitutional Court granted the petition for judicial review of the regulation to empty the religion column for indigenous faiths in family cards and electronic ID cards on November 7, 2017. This research focuses on the role of local religions in interfaith relations as a manifestation of religious moderation in Indonesia. Using qualitative data through literature study, this research explores the contribution of local religions in creating moderation, especially through moderation values that accommodate local wisdom. Local religions and moderation in religion can coexist, creating harmony in interfaith relations. This study highlights that ancestral and local religions have continued relevance in the face of changing times, making them important contributors to religious moderation and interfaith relations in Indonesia. By considering the Pancasila perspective of local religions, this study reveals how national values and history shape religious moderation. Meanwhile, local religions provide a foundation for building a harmonious society by raising awareness of relationships with nature and the environment. The findings suggest that history, nationality and the preservation of natural harmony by local religions simultaneously contribute to religious moderation in the context of local religions in Indonesia.